Analisa Kejahatan Streaming Ilegal Liga Inggris: Tantangan Hukum, Ekonomi Dan Dampak Pada Studi Kasus ZAL TV - Johana Jenni Viera; Salsabila Maryam; Hj. Lilik Prihatini, SH., MH (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract This journal documents and analyzes the case of illegal streaming of the English Premier League conducted by Ilham Allamsyah, the manager of Zal TV. Zal TV's streaming activities not only exploit gaps in streaming technology but also create serious issues related to copyright infringement and its impact on the Vidio platform industry. The case analysis method is employed to investigate the strategies and implications of Zal TV's illegal streaming. Legal review is conducted to understand the regulatory framework related to copyright and the Information and Electronic Transactions Law (ITE). Through content, impact, and legal analysis, it is revealed that Zal TV employs illegal servers to present English Premier League content without official permission, distributing it across various platforms, posing legal challenges in enforcement. Significant economic repercussions are observed on official broadcast rights holders like Vidio, leading to substantial financial losses. The conclusion emphasizes the necessity for a swift and effective response to illegal streaming. Robust copyright protection measures and law enforcement actions are required to ensure the sustainability of the entertainment industry. Consumer awareness of the negative impacts of illegal streaming can play a pivotal role in constructing a fair and sustainable digital environment.. Keywords: Zal TV, Vidio, Illegal Streaming, ITE Law, Copyright Abstrak Jurnal ini mendokumentasikan dan menganalisis kasus kejahatan streaming ilegal Liga Inggris yang dilakukan oleh Ilham Allamsyah selaku pengelola Zal TV. Streaming oleh Zal TV tidak hanya mengeksplorasi celah dalam teknologi streaming tetapi juga menciptakan masalah serius terkait hak cipta dan dampaknya pada industri platform Vidio. Metode analisis kasus untuk menyelidiki strategi dan implikasi streaming ilegal Zal TV. Tinjauan hukum dilakukan untuk memahami kerangka kerja regulasi terkait hak cipta dan UUITE. Melalui analisis konten, dampak, dan hukum. Zal TV menggunakan server ilegal untuk menyajikan konten Liga Inggris tanpa izin resmi. Ini mencakup distribusi melalui berbagai platform, yang memunculkan tantangan hukum dalam penegakan aturan. Dampak ekonomi yang signifikan terlihat pada pemegang hak siar resmi, seperti Vidio, dengan kerugian finansial yang mencuat. Kesimpulan dari penelitian ini menyoroti perlunya respons yang cepat dan efektif terhadap streaming ilegal. Langkah-langkah perlindungan hak cipta dan penegakan hukum yang kuat diperlukan untuk menjaga keberlanjutan industri hiburan. Kesadaran konsumen tentang dampak negatif dari streaming ilegal dapat menjadi kunci dalam membangun lingkungan digital yang adil dan berkelanjutan. Kata kunci: Zal TV, Vidio, Streaming Ilegal, UUITE, Hak Cipta